Situation Report: Bulgaria, 23 October 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Finnish Premier in Bulgaria Repatriation of Turks Continues Conference on Transport Problems Avramov Ends Asian Tour Economic Contacts Comings and Goings South Vietnamese "Revolutionary Government" Delegation in Bulgaria First Deputy Foreign Minister in Czechoslovakia Minister of Education in the Soviet Union